2007
DOI: 10.1097/aud.0b013e31803154d0
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Mandarin Hearing in Noise Test (MHINT)

Abstract: The two versions of the MHINT are the first standardized Mandarin sentence speech intelligibility tests. Similar to other language versions of the HINT, the MHINT was developed using the same rationale as the English HINT, allowing norm-referenced results for the MHINT to be compared directly with results in other languages. The MHINT would benefit from further evaluation of its validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(135 citation statements)
references
References 6 publications
6
127
1
1
Order By: Relevance
“…The "×" stands for row number and "−" stands for a test word. Chinese Mandarin Hearing in Noise Test (MHINT) (Wong et al, 2007) was used for the sentence intelligibility test. Every list contained 10 test sentences and each sentence was composed of 10 target words, for example, " (This team enters the finals at last)".…”
Section: Word Identification and Sentence Intelligibility Testmentioning
confidence: 99%
“…The "×" stands for row number and "−" stands for a test word. Chinese Mandarin Hearing in Noise Test (MHINT) (Wong et al, 2007) was used for the sentence intelligibility test. Every list contained 10 test sentences and each sentence was composed of 10 target words, for example, " (This team enters the finals at last)".…”
Section: Word Identification and Sentence Intelligibility Testmentioning
confidence: 99%
“…Although these differences were found to be statistically significant, they were all below 2 dB. This variability is primarily influenced by the step size used during adaptive testing (Wong et al, 2007). The step size in the current study was 2 dB, and the average difference between test and retest for all lists was therefore smaller than the adaptive step size, indicating an acceptable variability.…”
Section: Discussionmentioning
confidence: 88%
“…For this procedure, the noise was added to each sentence so as to ensure an SNR of -5 dB (noise 5 dB louder than speech). This level was chosen in accordance with the findings of previous researchers (Plomp & Mimpen, 1979;Nilsson et al, 1994;Kollmeier & Wesselkamp, 1996;Versfeld et al, 2000;Wong & Soli, 2005;Vaillancourt et al, 2005;Hällgren et al, 2006;Wong et al, 2007), who indicated that an SNR of -5 dB should yield an intelligibility score (defined in this instance as the percentage of syllables correctly discerned) of approximately 50%. Scoring each syllable provided a means of determining a percentage intelligibility score for each separate sentence.…”
Section: Methodsmentioning
confidence: 99%
“…The sentence material consisted of sentences taken from the Mandarin Hearing in Noise Test database (Wong et al, 2007). All the sentences were produced by a male speaker, with fundamental frequency ranging from 75 to 180 Hz.…”
Section: Subjects and Materialsmentioning
confidence: 99%